2016
DOI: 10.3832/ifor1691-008
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of environmental variability and ecosystem functional changes to interannual variability of carbon and water fluxes in a subtropical coniferous plantation

Abstract: Accurate quantification of the contribution of environmental variability and functional changes to the interannual variability of net ecosystem production (NEP) and evapotranspiration (ET) in coniferous forests is needed to understand global carbon and water cycling. This study quantified these contributions to the interannual variability of NEP and ET for a subtropical coniferous plantation in southeastern China, and the effect of drought stress on these contributions was also investigated. NEP and ET were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Species exploit different water use strategies in the trade‐off among water absorption, stomatal adjustment, leaf water potential, and carbon gain to adapt to varied soil moisture (Tang, Wen, Sun, Chen, & Wang, ; West et al, ; Zapater, Breda, Bonal, Pardonnet, & Granier, ). The root architecture system (Swaffer, Holland, Doody, Li, & Hutson, ; Yang, Wen, & Sun, ) and precipitation characteristics (Wu et al, ) are considered to be the essential factors influencing water uptake by plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Species exploit different water use strategies in the trade‐off among water absorption, stomatal adjustment, leaf water potential, and carbon gain to adapt to varied soil moisture (Tang, Wen, Sun, Chen, & Wang, ; West et al, ; Zapater, Breda, Bonal, Pardonnet, & Granier, ). The root architecture system (Swaffer, Holland, Doody, Li, & Hutson, ; Yang, Wen, & Sun, ) and precipitation characteristics (Wu et al, ) are considered to be the essential factors influencing water uptake by plant species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the substantial impacts of 2 of 26 climate extreme events (e.g., droughts, precipitation, wind storms, heat waves, frosts and fires) on the terrestrial carbon cycle have been revealed by a few recent studies [3,4]. These effects may alter the growth patterns of pine species and biodiversity as well as the structure and functioning of forest ecosystems [5,6], which will lead to a major impediment in our understanding of the underlying mechanisms causing the ongoing seasonal variation in carbon fluxes, mainly including gross primary production (GPP), ecosystem respiration (R) and net ecosystem exchange (NEE). Therefore, quantification of the carbon exchanges between the forest ecosystems and the atmosphere is challenging for current modeling techniques, due to the complex interactions and feedbacks involved in biological, physical and chemical processes across various spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%